2012
DOI: 10.4251/wjgo.v4.i4.84
|View full text |Cite
|
Sign up to set email alerts
|

Oncological outcomes of transanal local excision for high risk T1rectal cancers

Abstract: AIM:To evaluate the oncological outcomes of transanal local excision and the need for immediate conventional reoperation in the treatment of patients with high risk T1 rectal cancers. METHODS:Twenty five high risk T1 rectal cancers treated by transanal local excision at the Guangdong General Hospital were analyzed retrospectively. Twelve patients received transanal local excision and 13 patients underwent subsequent immediate surgical rescue after transanal local excision within 4 wk. Differences in the local … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…Pooled rates were calculated using 15 studies 8,10,14,28–30,34,38,40–44,47,49 reporting recurrence outcomes. Two studies 33,45 were excluded, as reported data were not specific to the cTME cohort.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Pooled rates were calculated using 15 studies 8,10,14,28–30,34,38,40–44,47,49 reporting recurrence outcomes. Two studies 33,45 were excluded, as reported data were not specific to the cTME cohort.…”
Section: Resultsmentioning
confidence: 99%
“…No significant difference was found between cTME and pTME resections for local (RR, 1.35; 95% CI, 0.70-2.61; p = 0.37), systemic (RR, 1.15; 95% CI, 0.50-2.66; p = 0.75), or all recurrence (RR, 1.13; 95% CI, 0.28-4.52; p = 0.86). Pooled rates were calculated using 15 studies 8,10,14,[28][29][30]34,38,[40][41][42][43][44]47,49 reporting recurrence outcomes. Two studies 33,45 were excluded, as reported data were not specific to the cTME cohort.…”
Section: Recurrencementioning
confidence: 99%
See 1 more Smart Citation
“…However, in the second case they found metastatic involvement in one out of six excised LN [ 15 ]. In the study by Wu et al ., assessing local recurrence rates of patients with high risk T1 rectal cancer (RC) after TEM, 15.4% of patients had mesorectal LN involvement (T1 RC patient reoperated after TEM within 4 weeks with unfavorable histopathological factors) [ 16 ]. In our study group, the average number of harvested LN was also 6.9 (range: 4–11) with no case of metastases.…”
Section: Discussionmentioning
confidence: 99%
“…In practice, transanal resection is usually only offered to those with T1 SM1/SM2 tumors that are well to moderately differentiated with no clinical or radiological evidence of lymphadenopathy [26]. Those with T1 SM3 or T2 tumors are at higher risk of local nodal involvement with subsequent higher rates of local recurrence when compared with traditional surgical approaches [27,28]. Accurate staging and patient selection are essential in this setting.…”
Section: Management Of Low-risk Diseasementioning
confidence: 99%